Association of periodontal health indicators and major depressive disorder in hospital outpatients - Amit Kumar; Asif Kardkal; Surangama Debnath; Jyothi Lakshminarayan (Wolters Kluwer Medknow Publications, 2015)
Background: Major depressive disorder (MDD) has been associated with changes in behavioral, neurophysiological, and neuroendocrinological factors and thought to be one of the leading causes of disability worldwide. There are various evidences that depression and periodontitis may also be related.Aim: The aim was to evaluate the association between MDD and periodontitis in a convenience sample of hospital outpatients. Materials and Methods: Sixty individuals (30 subjects with MDD and 30 subjects without MDD) of age 26-67 years were included in the study. Depression was assessed by means of structured clinical interview for diagnostic and statistical manual of mental disorders. The periodontal clinical examination included the number of missing teeth, plaque index, gingival index (GI), probing pocket depth, and clinical attachment level (CAL). Results: Mean number of missing teeth per patient was 1.14 (±1.2 standard deviation [SD]) in the control group and 2.58 (±1.64 SD) in case group (P < 0.001). The amount of plaque was significantly higher in cases compared with control (P = 0.001). The patients had an average GI of 1.82 (±0.65 SD) compared to 1.14 (±0.81 SD) for the controls (P < 0.001). Mean probing depth and CAL were 4.67 (±0.8 SD) mm and 4.96 (±0.2 SD) mm in the case group and 2.6 (±2.2 SD) mm and 2.7 (±0.43 SD) mm in the control group, respectively (P < 0.05). Conclusion: Our study confirms the significant association between depression and periodontitis and depression can be considered one of the important risk factors for periodontal diseases.